CRITICAL DISCOURSE ANALYSIS OF INTERPERSONAL MEANING AND IDEOLOGY IN ANNUAL REPORTS OF SELECTED COMMERCIAL BANKS (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This research examines the interpersonal meaning embedded in the statements of the Chief Executive Officers of four selected Nigerian commercial banks - Fidelity Bank, Guaranty Trust Holding Company, Stanbic Bank and Sterling Bank, contained in their most recent annual reports of 2021. Halliday’s interpersonal metafunction and Fairclough’s three-dimensional framework of critical discourse analysis were used as theoretical frameworks. The interpersonal metafunction realized through the lexicogrammatical features of mood and modality is used to investigate ideological structures in these statements while the three-dimensional framework was used to describe, interpret and explain the data for this research. The findings reveal that the statements achieve their interpersonal meaning of giving information as more declarative mood choices are recorded. Through the mood structure, these Chief Executive Officers portray the banks they represent as being made up of a closely-knit team of corporate individuals working for the good of customers who are at the receiving end of their powerful services. The study concludes that commercial bank language is ideologically loaded and is construed to inform, convince, persuade and inspire loyalty and trust in their brands from shareholders and customers.
Keywords: ideology,power,systemicfunctionalgrammar,interpersonalmeaning,commercialbanks,bankingdiscourse